Efektivitas Job Design Pada Employee Engegement Terhadap Kinerja Karyawan: Studi Literatur - Muhammad Ade Kurnia Harahap; Udi Iswadi; Muhammad Fatkhurohman Albashori; Wahyudiyono Wahyudiyono; Nelli Roza (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effectiveness of Job Design on Employee Engagement on Employee Performance by means of a literature study. The method used in this research is library research by reviewing some of the results of previous research sourced from domestic and international articles with the support of the Google Schoolars search engine and Mendeley reference analysis. From the results of an analysis of several human resource management literatures that specifically discuss job design and employee engagement on employee performance, all references to previous studies show that job design and employee engagement have a significant effect on employee performance. Job design determines the relationship between managers and employees as well as the relationship between the employees themselves. Because with a clear job design, employee engagement will emerge in employees which will later have an impact on their performance as seen by how employees are fully immersed in their work and organization that are connected both physically, emotionally and cognitively. Keywords: Employee Engegement, Job Design, Employee Performance, Literature Study.